The role of the surgeon in treating patients with lung cancer. An updating article - Pêgo-Fernandes, Paulo Manuel; Haddad, Fabio José; Imaeda, Carlos Jogi; Sandrini, Marcel (São Paulo Medical Journal, 2021)
Lung cancer is a type of neoplasia with one of the highest incidences worldwide and is the largest cause of mortality due to cancer in the world today. It is classified according to its histological and biological characteristics, which will determine its treatment and prognosis. Non-small cell lung cancer accounts for 85% of the cases, and these are the cases that surgeons mostly deal with. Small cell lung cancer accounts for the remaining 15%. Surgery is the main method for treating early stage lung cancer, and lobectomy is the preferred procedure for treating primary lung cancer, while sublobar resection is an alternative for patients with poor reserve or with very small tumors. Surgeons need to be trained to use the resources and techniques available for lung resection, including less invasive approaches such as video-assisted thoracoscopic surgery (VATS) and robotic-assisted thoracoscopic surgery (RATS), and need to be familiar with new oncological approaches, including curative, adjuvant or palliative treatments for patients with lung cancer.